A New Homozygous Mutation (c.393-394del TA/c.393-394del TA) in the NT5C3 Gene Associated With Pyrimidine-5′-Nucleotidase Deficiency: A Case Report. Issue 8 (November 2019) - Köker, Sultan A.; Oymak, Yeşim; Bianchi, Paola; Fermo, Elisa; Karapinar, Tuba H.; Gözmen, Salih; Ay, Yilmaz; Vergin, Raziye C.
Abstract : Pyrimidine-5-nucleotidase (P5′N-1) deficiency is a rare nonspherocytic hemolytic anemia due to pyrimidine nucleotide deposition within erythrocytes. This rare erythrocyte disorder shows autosomal recessive inheritance with mutation of the pyrimidine-5′-nucleotidase gene, which is localized on 7p15-p14. Consanguinity of parents increases the probability of disease with novel mutations. Here, we report a 12-year-old boy with a delayed diagnosis of P5′N deficiency whose parents were consanguineous. He had a hemoglobin level of 7.5 g/dL, mean corpuscular volume of 93 fL, 7% reticulocyte, and lactate dehydrogenase of 678 IU/L. A peripheral blood smear showed polychromasia, marked anisopoikilocytosis with schistocytes, elliptocytes, stomatocytes, spherocytes, dacryocyte, and basophilic stippling in red blood. Decreased purine/pyrimidine ratio was 1.07 (normal range=1.4 to 2.98). Molecular analysis with direct DNA sequencing of the NT5C3 gene, codifying for P5′N-1, revealed the presence of a novel homozygous mutation, c393-394delTA, in the gene coding P5′N enzyme in the patient. To our knowledge, this is a newly defined mutation in P5′N deficiency.